Tinjauan Hukum Waris Islam Dalam Penundaan Pembagian Harta Warisan: (Studi Kasus di Kelurahan Koya Timur, Distrik Muara Tami, Kota Jayapura) - Bambang Edi Tilarsono; Husnul Yaqin; Amri Amri (ISTIDLAL, 2022)
The provisions regarding inheritance in Islam are one of the provisions that have been described clearly and in detail, even Allah SWT ordered them to immediately implement them. This research aims to find out aspects of the trigger for inheritance not being distributed immediately and the views of Islamic law regarding the behavior of the East Koya people who do not immediately give inheritance to those who are entitled to receive it. This field research is sociological research of Islamic law. Information was collected using interview, observation, and documentation methods. After the information is collected, it is analyzed using data collection methods, data reduction, data presentation and conclusions, and analyzed using Islamic Law analysis. The results of this research are: First, the factors that delay the distribution of inheritance are: (a) the lack of deliberation between the heirs, (b) one of the parents is still alive, (c) the child is considered unable to carry out the inheritance, (d) the inheritance managed together, and (e) the lack of knowledge about the jurisprudence of the Mawaris. Second, the law delaying the distribution of inheritance by the Koya Timur community after fulfilling the rights of the deceased is unlawful or not justified by Islamic Shari'ah. This is because the instructions are clear both in the Qur'an and the Hadith of the Prophet SAW and in Article 175 of the Compilation of Islamic Law to immediately give inheritance to anyone who is entitled to receive it. In the rules of ushul fiqh it is also explained that the origin of the command is obligatory, so when someone does not carry out the obligatory command, it will be a sin.